The pervasiveness of interleukin-1 in Alzheimer pathogenesis: a role for specific polymorphisms in disease risk - Griffin, W.S.T. (2000)
Interleukin-1 (IL-1) has been implicated as a key molecule in Alzheimer pathogenesis based on findings of an IL-1 overexpression in Alzheimer brain that is directly related to plaque progression and tangle formation, and on findings that IL-1 induces excessive synthesis, translation, and processing of neuronal β-amyloid precursor protein (βAPP) as well as synthesis of most known plaque-associated proteins. In addition, IL-1 activates astrocytes, with the important consequence of over-expression of the neuritogenic cytokine S100β and overgrowth of dystrophic neurites in neuritic plaques. As further evidence of the importance of IL-1 in Alzheimer pathogenesis, two new genetic studies of inheritance of specific polymorphisms in IL-1 genes in Alzheimer and control patients show that homozygosity for a specific IL-1A gene polymorphism at least triples risk for development of Alzheimer’s disease. This increase is associated with earlier age of onset. Homozygosity for this polymorphism plus another in the IL-1B gene further increases risk.